Regeneration, growth of Hill Sal and plant diversity in Community Forest: A case study from Pragatisil Community Forest in Kaski District, Western Nepal - Paudyal, B. K. (Banko Janakari, 2016)
The study was conducted in the Pragatisil Community Forest, Kaski District, Nepal in 2012 to assess the regeneration status of Sal (Shorea robusta) seedlings, its growth and plant diversity. A plot size of 25 m × 20 m was employed for trees, 10 m ×10 m for poles and 5 m × 5 m for regeneration. The growth parameters measured were dbh and height. A factorial arrangement of treatments was employed; the treatments being slope and aspect. The results showed that there was significant (p<0.05) effect of slope on dbh and basal area whereas there was no effect of aspect on growth parameters measured in the Pragatisil Community Forest. The regeneration of Sal was satisfactory (6,126 seedlings/ha), and there were 32 plant species in this forest. As there was higher basal area per ha in the Pragatisil Community Forest, it is recommended to have thinning of 40% of basal area for enhancing growth of remaining stems. Banko Janakari, Vol. 23, No. 2, 2013